2019
DOI: 10.1038/s41467-019-08344-5
|View full text |Cite
|
Sign up to set email alerts
|

Membrane reshaping by micrometric curvature sensitive septin filaments

Abstract: Septins are cytoskeletal filaments that assemble at the inner face of the plasma membrane. They are localized at constriction sites and impact membrane remodeling. We report in vitro tools to examine how yeast septins behave on curved and deformable membranes. Septins reshape the membranes of Giant Unilamellar Vesicles with the formation of periodic spikes, while flattening smaller vesicles. We show that membrane deformations are associated to preferential arrangement of septin filaments on specific curvatures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
106
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(123 citation statements)
references
References 43 publications
15
106
1
1
Order By: Relevance
“…Septins can distinguish positive membrane curvatures at the micron-scale without any other cellular factors . When purified septins are mixed with membranes at a range of different curvatures, septins polymerize into aligned filaments wrapped at an optimal curvature (Beber et al, 2019;Cannon et al, 2019;Tanaka-Takiguchi et al, 2009). However, individual septin complexes can distinguish membranes with micron-scale curvature which manifests through septin-membrane binding kinetics (Cannon et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Septins can distinguish positive membrane curvatures at the micron-scale without any other cellular factors . When purified septins are mixed with membranes at a range of different curvatures, septins polymerize into aligned filaments wrapped at an optimal curvature (Beber et al, 2019;Cannon et al, 2019;Tanaka-Takiguchi et al, 2009). However, individual septin complexes can distinguish membranes with micron-scale curvature which manifests through septin-membrane binding kinetics (Cannon et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Septin proteins and filaments are known to interact directly with membrane lipids 13,[70][71][72]78 , accumulating at locations with positive curvature 18,79,80 . This direct interaction can be mediated by a polybasic region of septins interacting with acidic head groups of phospholipids on the membrane surface 81 .…”
Section: Septin -Membrane Interactionsmentioning
confidence: 99%
“…Bin-Amphiphysin-Rvs domain-containing proteins) that detect curvature at the nanometer scale (McMahon and Boucrot, 2015). Interestingly, new work has shown that an amphipathic helix (AH) is necessary and sufficient for septin curvature sensing both in vitro and in vivo (Cannon et al, 2019), and that septin filaments can reorganize in response to changes in membrane curvature (Beber et al, 2019). Considering their important roles in health and disease (Hall and Russell, 2004;Mostowy and Cossart, 2012;Peterson and Petty, 2010), how septins assemble and how they work in conjunction with actin, microtubules and phospholipids, are the focus of intense investigation.…”
Section: Septin Biologymentioning
confidence: 99%